Expressive Writing Dapat Menurunkan Kecemasan Remaja Selama Pembelajaran Daring di Pandemi Covid-19: Expressive Writing Can Reduce Adolescent Anxiety During Online Learning in The Covid-19 Pandemic - Mutiara; Eka Rokhmiati; Irma Herliana (Dohara POAJ, 2021)
Introduction: Expressive writing is a coping to overcome anxiety especially when going to face school exams. Methods: The design of this study used Quasi-Experimental with One group pretest-posttest design approach in 30 respondents, and the instrument used was questionnaire. The standard questionnaire method used to measure anxiety is Zung Self-Rating Scale Anxiety. Analysis of this research using Paired T Test. Results: From the results of univariate analysis tests there was anxiety after the intervention of 30 respondents experienced mild anxiety. From the results of bivariate test obtained the results of the influence of expressive writing interventions on decreased anxiety with P value = 0.001. Discussion: From the results of the study, it can be concluded that there is a decrease in anxiety after expressive writing interventions.